2019
DOI: 10.3390/cells8060548
|View full text |Cite
|
Sign up to set email alerts
|

Capturing the Biologic Onset of Inflammatory Bowel Diseases: Impact on Translational and Clinical Science

Abstract: While much progress has been made in the last two decades in the treatment and the management of inflammatory bowel diseases (IBD)—both ulcerative colitis (UC) and Crohn’s Disease (CD)—as of today these conditions are still diagnosed only after they have become symptomatic. This is a major drawback since by then the inflammatory process has often already caused considerable damage and the disease might have become partially or totally unresponsive to medical therapy. Late diagnosis in IBD is due to the lack of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 118 publications
(169 reference statements)
0
7
0
Order By: Relevance
“…The balance between beneficial gut commensals and pathogens is crucial to human health. The dysbiosis of gut microbiota contributes to gut inflammation and may be closely related to the onset and progression of CD [ 4 , 5 , 7 ]. However, our understanding of the relationship between gut microbiota and CD is still relatively poor as it is difficult to detect and diagnose CD in the biologic onset or early stage of disease (e.g., preclinical) [ 5 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The balance between beneficial gut commensals and pathogens is crucial to human health. The dysbiosis of gut microbiota contributes to gut inflammation and may be closely related to the onset and progression of CD [ 4 , 5 , 7 ]. However, our understanding of the relationship between gut microbiota and CD is still relatively poor as it is difficult to detect and diagnose CD in the biologic onset or early stage of disease (e.g., preclinical) [ 5 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that the changes in the abundance of Bacteroides in CD patients were controversial. The increased abundance of Bacteroides in the CD group compared with health participates was related to the maintenance of postoperative remission [ 4 , 29 ]. However, other studies provided that the abundance of Bacteroides in CD patients was reduced [ 27 , 30 ]; B. thetaiotaomicron , belonging to the Bacteroides was found to prevent weight loss, colonic histopathological changes and the production of inflammatory factors in a mouse enteritis model induced by dextran sodium sulfate (DSS) [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations